Small Ruminant Models for Articular Cartilage Regeneration by Scaffold-Based Tissue Engineering. (6th December 2021) - Peng, Liqing; Zhang, Bin; Luo, Xujiang; Huang, Bo; Zhou, Jian; Jiang, Shuangpeng; Guo, Weimin; Tian, Guangzhao; Tian, Zhuang; Shen, Shi; Li, Yangyang; Sui, Xiang; et al.
Abstract : Animal models play an important role in preclinical studies, especially in tissue engineering scaffolds for cartilage repair, which require large animal models to verify the safety and effectiveness for clinical use. The small ruminant models are most widely used in this field than other large animals because they are cost-effective, easy to raise, not to mention the fact that the aforementioned animal presents similar anatomical features to that of humans. This review discusses the experimental study of tissue engineering scaffolds for knee articular cartilage regeneration in small ruminant models. Firstly, the selection of these scaffold materials and the preparation process in vitro that have been already used in vivo are briefly reviewed. Moreover, the major factors influencing the rational design and the implementation as well as advantages and limitations of small ruminants are also demonstrated. As regards methodology, this paper applies principles and methods followed by most researchers in the process of experimental design and operation of this kind. By summarizing and comparing different therapeutic concepts, this paper offers suggestions aiming to increase the effectiveness of preclinical research using small ruminant models and improve the process of developing corresponding therapies.